(untitled) (Shahroud Journal of Medical Sciences, 2024)
Background: The present study aimed to investigate the effectiveness of cognitive rehabilitation on improving executive actions, performance, and attitude toward reading in children with dyslexia. Methods: In terms of nature, the research method is practical and semi-experimental. The research design was pre-test-post-test with the control group. The statistical population includes all male and female students between the ages of 8 and 12 who were dyslexic and referred to learning disabilities centers in Shahroud City in 2023, from which a sample of 30 people was selected purposefully. The data collection tool was the behavioral rating questionnaire of executive actions, the official test of reading and dyslexia (Karma Nouri and Moradi, 2017), and the attitude test toward reading (McKenna and Kerr, 1990). The experimental group underwent cognitive rehabilitation training for children with dyslexia using working memory software for 11 sessions of 60 minutes, and the control group did not receive training during this period. For data analysis, univariate and multivariate analysis of covariance and Bonferroni post hoc test were used with the help of SPSS26 software. Results: The results showed that cognitive rehabilitation training improved executive actions, reading performance, and attitude toward reading in dyslexic children. Therefore, it is suggested to use computer-aided cognitive rehabilitation due to its attractive environment and sound, image, and video for children with special needs who have a low threshold of patience and attention. Conclusions: Because these children get tired and bored during training and need a strong stimulus to continue training, it is necessary to provide rewards at the time of success and by giving immediate feedback at the moment of failure.